MYCORRHIZAL SYMBIOSIS ALTERS ROOT H EFFLUXES AND ROOT SYSTEM ARCHITECTURE OF TRIFOLIATE ORANGE SEEDLINGS UNDER SALT STRESS - Qiang-Sheng Wu; Ying-Ning Zou (Journal of Animal and Plant Sciences, 2013)
H + fluxes are important for exchange of nutrients and regulation of cytosolic pH and cell wall plasticity. Root systemarchitecture (RSA) is a deciding factor in water- and nutrient-uptaked efficiency of a plant. Four-month-old trifoliate orange (Poncirus trifoliata L. Raf.) seedlings inoculated with or without an arbuscular mycorrhizal fungus (Funneliformis mosseae) were conducted to analyze root H+ effluxes and RSA under the conditions of 100 mM NaCl, 100 mM KCl, and 100 mM NaNO3. Although salt stress partly inhibited growth performance (plant height, stemdiameter, and leaf number) and RSA variables (length, projected area, surface area, volume, and average diameter), mycorrhizal inoculation generally significantly increased these growth performance and RSA traits. There was a more acid environment in rhizosphere of mycorrhizal seedlings than in non-mycorrhizal seedlings, based on bromocresol purple dyeing. The root H+ efflux rates were significantly increased by the salt treatments. On the other hand, F. mosseae significantly increased the root H + efflux rates by 14.3%, 31.7%, 10.3%, and 16.7% under the NaCl, KCl, NaNO3 and non-salt conditions, respectively. It is concluded that mycorrhizal symbiosis increased root H + effluxes and improved RSA of trifoliate orange seedlings under salt stress, which might enhance salt tolerance of the host plant.
Keywords: Arbuscular mycorrhizal fungi; Citrus; H efflux rates; Root system; Salt stress